Effect of Spinal and General Anesthesia on Postoperative Pain and Satisfaction in Ureteroscopic Lithotripsy (URSL) - Tavoosian, Ali; Shamshirgaran, Amirreza; Hosseini, Seyed Reza; Alaedini, Farshid; Aghamir, Seyed Mohammad Kazem (Urology Journal, 2025)
Purpose: To compare general anesthesia (GA) with spinal anesthesia (SA) regarding postoperative pain and satisfaction after ureteroscopic lithotripsy (URSL). Materials and Methods: Two hundred twenty-nine patients were analyzed in the study. Patients were assigned to two groups—SA and GA. Demographic data, stone characteristics, operation time, and frequency of opioid analgesic use during the admission period were collected from hospital medical records. Visual analogue scale (VAS) scores at 6 hours and 24 hours after URSL were recorded. Complications according to the Clavien–Dindo classification and the experience of headaches after surgery (Yes/No) were documented after one month. Participants and surgeons were asked to rate their satisfaction on a scale of 1 to 10. Results: Of 237 eligible patients, 229 completed the study. The incidence of headaches and VAS scores (at 6 h and 24 h) were significantly higher in the SA group (P < 0.001). Patient and surgeon satisfaction in the GA group were significantly higher (P < 0.001). Multivariate analysis showed that female sex was associated with lower opioid analgesic use during the admission period (odds ratio [OR] = 0.47), and surgery time correlated with frequency of opioid use and headache (OR = 1.12 and OR = 1.11, respectively). Conclusion: GA was associated with better postoperative pain control after URSL and higher satisfaction levels for both surgeons and patients.